Dose calculation and measurement from B10(n,α)Li7 reaction using filtered neutron beam at Dalat Nuclear Research Institute - Trịnh, Thị Tú Anh (2022)
In this research, dose calculation and measurement from B10 (n,α) Li7 reaction using filtered neutron beam at Dalat Nuclear Research Institute have been reported. Calculation was carried out by using Monte Carlo method. Neutron activation technique using vanadium foil was employed to determine neutron flux at various positions in phantom from which neutron dose has been calculated using conversion factor. These calculations are basics for the dose determination research of the Boron Neutron Capture Therapy (BNCT) in Vietnam.